DIAGNOSTIC APPROACH TO ARTERIAL HYPERTENSION OF SUSPECTED SECONDARY CAUSE IN PRIMARY HEALTH CARE - HYPERTENSION OF RENAL CAUSE - Silva, Rita (2024)
Renal pathology is one of the leading causes of secondary arterial hypertension. Hypertension of a renal cause can originate in the renal parenchyma or the renal artery and is called renal parenchymal hypertension or renovascular hypertension, respectively. The presence of hypertension is common in kidney diseases, being a critical prognostic factor, so its diagnosis, treatment and adequate guidance are essential. The role of General and Family Medicine in the initial assessment of patients with hypertension of a renal cause and the management of the disease is fundamental, namely, in the implementation of the correct treatment, as well as in the timely referral to the specialized consultation in the hospital environment, when necessary.